Construction of MXene/PDMS‐Based Triboelectric Nanogenerators for High‐Performance Cathodic Protection - Hui Xu; Xiutong Wang; Jianmin Niu; Youbo Nan; Jiayan Pu; Hui Zhou; Jizhou Duan; Yanliang Huang; Baorong Hou (Advanced Materials Interfaces, 2022)
Abstract A vertical contact‐separation mode triboelectric nanogenerator (TENG) to collect mechanical energy and protect stainless steel from corrosion is constructed by spraying to combine MXene powder and polydimethylsiloxane (PDMS). The output of TENG increases significantly by spraying a very small amount (1.2 mg) of MXene, which has excellent conductivity and electro‐negativity. The MXene/PDMS TENG (MP/PP‐TENG) shows the output performance with a short current circuit of 22 µA and output voltage of 900 V, and the output peak power increases by 2.6 times. Meanwhile, MP‐TENG is a reliable alternative to power supply for cathodic protection. The electrochemical measurement results show that the open circuit potential drop of the stainless steel coupled with the MP‐TENG is about 300 mV. Continuous motion of TENG can realize processive protection of metals, proving its potential practical application to all‐weather marine corrosion protection.